ANALISIS SEMIOTIK IKLAN PARIWISATA NEGARA AUSTRALIA - Anak Agung Istri Manik Warmadewi (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2019)
[Title: Semiotic analysis on Australian tourism advertisement] The aim of this study is to analyze the "signifier and signified which contain in two Australian tourism advertisements. Each of them has their own theme, those are â€œZoo without Fencesâ€ and â€œMeet the Localsâ€. The method that is used in collecting the data is documentation method and to analyze the data in this study, semiotic analysis method is used which relies to Roland Barthes theory, for signifier, signified, denotation and connotation. Based on final identification and data analysis, can be known that all advertisements have the same denotation meaning but different connotation meaning. The connotation meaning for each advertisement is different to other advertisement. For example, first advertisement has connotation meaning unlimited tranquility and freedom in Kangaroo Island. While the second advertisement means feeling the patienty of local habitant of Australia.